A study and comparison of bioimpedance parameters during foot massage reflexology using aroma oil / Saeed Ahmed - Saeed, Ahmed (2012)
Massage is one of the most common therapeutic techniques for muscle relaxation and pain reduction. It is used for maintaining the condition of the body and treating human diseases for thousands of years. Foot massage basically is a massage treatment around the calf muscle until underneath foot area where it initiates stimulation to anatomical organs. In this thesis, the bio impedance parameters (BI) of people undergoing reflexology therapy are analyzed. A comparison between bio impedance (BI) parameters of a subject using aroma oil is measured before and after the massage, to see improvement of the hydration level of cells. The measurement of bio impedance parameters is done by using Bodystat Quadscan 4000. The main purpose of this study is to investigate the effect of reflexology in terms of resistance (R); reactance (X); impedance (Z); Phase angle; and capacitance (C) of male and female subjects that can be measured as bio impedance (BI) parameters. All these parameters are analyzed by using statistical analysis program called SPSS. The result showed that there is significant difference between the mean of each bio impedance parameters of before and after massage therapy. This makes us conclude that conclude that reflexology massage treatment does have a significant effect in improving cell hydration levels.